Legal and Ethical Considerations in the Conservation of Artwork Produced During Art Therapy. Issue 3 (3rd July 2022) - McCann, Laura; Stein, Chantal; Pace, Jessica; Wolf, Andy; Parks, Katherine
ABSTRACT: Works of art created by children under the care of art therapy pioneer Edith Kramer at the Wiltwyck School for Boys in the 1950s are presented as a case study to examine the practical, legal, and ethical challenges of conserving art produced in the course of therapy. The artworks, deposited in the New York University Libraries Special Collections in 2011, are five drawings and forty-two paintings on paper. Multidisciplinary research into the fields of art therapy, archival management, health care law, and the history of Wiltwyck revealed a broad spectrum of value categories associated with the artworks. A values-based decision-making process, together with information garnered through materials testing and analysis, informed conservation actions, including the retention of post-custodial interventions and redaction of private health information.